2023
DOI: 10.3390/medicina59020284
|View full text |Cite
|
Sign up to set email alerts
|

Potential Drug-Drug Interactions among Patients with Schizophrenia Spectrum Disorders: Prevalence, Association with Risk Factors, and Replicate Analysis in 2021

Abstract: Background and Objectives: Patients with schizophrenia are often exposed to polypharmacotherapy, which may lead to drug—drug interactions. The aim of the study was to investigate the prevalence of potential drug—drug interactions (pDDIs) in hospitalized patients with schizophrenia spectrum disorders and to identify factors associated with pDDIs and manifested symptoms and signs. Materials and Methods: This cross-sectional observational study included 311 inpatients admitted to a psychiatric hospital. The LexiC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Patients with schizophrenia often receive polypharmacotherapy, exposing them to potential drug–drug interactions (DDIs). A cross-sectional observational study in a psychiatric hospital found a high prevalence (88.7%) of potential DDI in this population ( Bačar Bole et al, 2023 ). Clozapine is metabolized by various CYP450 enzymes, including CYP1A2, CYP3A4, CYP2D6, CYP2C9, and CYP2C19 ( Chetty and Murray, 2007 ; Pardiñas et al, 2019 ).…”
Section: Introductionmentioning
confidence: 89%
“…Patients with schizophrenia often receive polypharmacotherapy, exposing them to potential drug–drug interactions (DDIs). A cross-sectional observational study in a psychiatric hospital found a high prevalence (88.7%) of potential DDI in this population ( Bačar Bole et al, 2023 ). Clozapine is metabolized by various CYP450 enzymes, including CYP1A2, CYP3A4, CYP2D6, CYP2C9, and CYP2C19 ( Chetty and Murray, 2007 ; Pardiñas et al, 2019 ).…”
Section: Introductionmentioning
confidence: 89%
“…Another study also found no significant relationship between gender and age with potential drug interactions (44) . However, studies in Ethiopia and Pakistan, Slovenia, Brazil found a significant relationship between the number of drugs and the potential for drug interactions, where an increase in the number of drugs corresponded to an increase in the potential for drug interactions (45)(46)(47) . The difference in results could be due to the potential drug interactions studied in our study focusing only on the potential drug interactions involving antihypertensive and antidiabetic drugs.…”
Section: Appropriateness Of Antihypertensive and Antidiabetic Drug Se...mentioning
confidence: 98%
“…Pharmacological treatments are available for management of OAS but may be limited by tolerability, presence of physical comorbidities, and potential adverse effects of polypharmacy [ 5 , 6 ]. A more recent study has indicated that patients with old-age onset schizophrenia share a unique clinical course and treatment response compared to the general schizophrenia population [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%